Traumatic brain injury in pediatric patients –Clinical manifestations and outcome - Arijit Ghosh; Aniruddha Chattopadhyay; Jayanta Ghosal; Sumanta Sarkar (Asian Journal of Medical Sciences, 2022)
Background: Pediatric traumatic brain injury (TBI) is a global public health concern and is preventable, but there are no approved therapies to treat it definitely until date. Falls are the most frequent mode of injuries followed by road traffic accidents (RTA). Most of the TBIs have favorable outcome, though this is influenced by geographical, environmental, societal, and ethnic differences. Aims and Objectives: The aims of this study were to determine the several modes of injury, severity of injury, outcomes, and complications in the Eastern Indian population. Materials and Methods: Children-aged <18 years suffering from TBI who were attended to in Bangur Institute of Neurosciences, Institute of Post-Graduate Medical Education and Research, Kolkata, were prospectively studied for 1 year. Detailed history, clinical examinations, assessment of pupillary status, and Glasgow Coma Scale (GCS) score was recorded. Severity of TBI was done based on GCS score for each case. Computed tomography (CT) scan of head without contrast was the initial mode of neuro imaging and findings were recorded diligently. Patients were treated conservatively and surgically as required. Outcome was assessed in relation to age group, gender, initial GCS score, pupillary status, CT findings, intervention, and associated injuries. Simple statistical analysis was done. Results: Among the total 150 patients aged 1–18 years, most common mode of injury was fall in 56.66% followed by RTA in 23.33%, assault in 6.66%, and other modes such as sports, hit by object on head, and firearm injury in 13.33%. RTAs had a poor outcome in 14.29% and fall had a poor outcome in 14.12%. Poor outcome was associated with the highest (68%) being midline shift (MLS)>3 mm and it was 12.77% with MLS of <3 mm and it was 10.26% in patients with no MLS. It was noticed that chest, spinal, and multiple injuries were associated with poor outcome. Conclusion: The most important prognostic factors regarding pediatric TBI are GCS at presentation, pupillary status, associated injuries, and CT scan findings.